A COMPARATIVE STUDY OF THE IMPLEMENTATION OF DEEP LEARNING IN INTERNATIONAL KINDERGARTENS IN INDONESIA AND SOUTHERN THAILAND - Vioren Irodatus Sakinah; Muniroh Munawar; Anita Chandra Dewi Sagala (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Global changes in education demand learning strategies that can develop 21st-century skills, making the deep learning approach increasingly relevant in fostering conceptual understanding and meaningful learning experiences. This study compares the implementation of deep learning in early childhood education at PG-TK Semesta International School, Indonesia, and Satit Phatna Witya School, Southern Thailand, to identify similarities, differences, and factors influencing their success. The study employed a descriptive qualitative method with a comparative study design, utilizing observation, interviews, and documentation, which was then analyzed using the Miles and Huberman model. The results show that both schools apply deep learning principles with different approaches: PG-TK Semesta emphasizes learning by doing through projects and environmental exploration, while Satit Phatna Witya integrates cultural values ​​and utilizes technology in its learning process. Supporting factors include the role of teachers as facilitators, a conducive learning environment, technological support, and a positive school culture. Meanwhile, the barriers include variations in children's abilities, limited teacher understanding, language differences, and unequal learning resources. This research demonstrates that the success of deep learning is determined by teacher readiness, environmental support, and contextual learning strategies. This research also helps advance the use of adaptable deep learning methods in early childhood education.